2021
DOI: 10.3390/biom11111604
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Hypoxia: Revival of Old Remedies

Abstract: Tumour hypoxia is significantly correlated with patient survival and treatment outcomes. At the molecular level, hypoxia is a major driving factor for tumour progression and aggressiveness. Despite the accumulative scientific and clinical efforts to target hypoxia, there is still a need to find specific treatments for tumour hypoxia. In this review, we discuss a variety of approaches to alter the low oxygen tumour microenvironment or hypoxia pathways including carbogen breathing, hyperthermia, hypoxia-activate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 188 publications
0
9
0
Order By: Relevance
“…13,14 For more than a century, extensive efforts have been made to address tumor hypoxia in both experimental and clinical settings. 15 The key is to develop therapies that aim to target the hypoxic environment and improve intratumoral oxygenation to inhibit tumor progression and treatment resistance. To target hypoxic cells, inhibitors of hypoxia-related pathways, such as HIFs and mammalian target of rapamycin (mTOR), have been developed.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…13,14 For more than a century, extensive efforts have been made to address tumor hypoxia in both experimental and clinical settings. 15 The key is to develop therapies that aim to target the hypoxic environment and improve intratumoral oxygenation to inhibit tumor progression and treatment resistance. To target hypoxic cells, inhibitors of hypoxia-related pathways, such as HIFs and mammalian target of rapamycin (mTOR), have been developed.…”
Section: Introductionmentioning
confidence: 99%
“…For more than a century, extensive efforts have been made to address tumor hypoxia in both experimental and clinical settings 15 . The key is to develop therapies that aim to target the hypoxic environment and improve intratumoral oxygenation to inhibit tumor progression and treatment resistance.…”
Section: Introductionmentioning
confidence: 99%
“…As it was mentioned by Tharmalingham, H. et al [ 64 ], the use of nimorazole as a radiosensitizer was a standard practice in Denmark alone, as Danish research confirmed its safety in the treatment of, e.g., supraglottic and pharynx tumors. Recently, new clinical trials with nimorazole in Denmark and the UK have also been reported, but it is still necessary to assess whether this drug directly changes the oxygenation status of patient tumors [ 65 ].…”
Section: Hypoxia-activated Prodrugs (Haps)mentioning
confidence: 99%
“…Hypoxia-activated prodrugs (HAPs) are bioreductive drugs that are selectively reduced by reductases under hypoxic conditions to form cytotoxic compounds that kill hypoxic tumor cells (Denny, 2000;Denny, 2010;Hunter et al, 2016;Phillips, 2016;Baran and Konopleva, 2017;Mistry et al, 2017;Jackson et al, 2019;Li et al, 2021a;Anduran et al, 2021;Li et al, 2021b;Codony and Tavassoli, 2021). This bio-reductive process is inhibited by oxygen preventing the complete reduction of the compound into its active form (Vilaplana-Lopera et al, 2021). In other words, HAPs should not be toxic for normal oxygenated tissues.…”
Section: Prodrugs Activated In Hypoxic Cellsmentioning
confidence: 99%